In Vitro Corrosion of Quaternery Magnesium Alloy Foam by Addition of Zinc - Franciska Pramuji Lestari; Sofia Marta; Aprilia Erryan; Inti Mulyati; Ika Kartika (Department of Electromedical Engineering, POLTEKKES KEMENKES SURABAYA and IKATEMI, 2020)
Magnesium alloys have been intensively studied as possible resorbable material with adequate mechanical properties similar to natural bones but very poor corrosion properties. In this analysis, the addition of Zn element to quaternary Mg-Ca-Zn alloy foam was evaluated with TiH2 as a foaming agent and manufactured with high-purity raw materials the powder metallurgy process. In Hank's solution, the rate of corrosion of specimens by direct observations with Scanning Electron Microscopy ( SEM), Electron Dispersion Spectrometry (EDS), static immersion studies, potentiodynamic evaluations, and X-Ray Diffraction (XRD). The specimens post-immersion characteristics and the corresponding Hank's solutions were examined at 2, 4, 6, 24, 48, and 72 hours of immersion. The findings show that the microstructure of alloy morphology, such as pores, pitting corrosion, needle shapes, and galvanic corrosion has the main corrosion products Mg(OH)2 and Ca10(PO4)6(OH)2. The addition of less than 6 percent wt Zn will minimize the corrosion rate but increase with 10 percent wt Zn. From this study, Mg-Zn-Ca alloy at 6 percent wt Zn has the lowest corrosion rate with slow pH changes in the process.